Magnitude of change in cardiac health-enhancing behaviours six months following an acute myocardial infarction - Salamonson, Y.; Everett, B.; Davidson, Patricia; Andrew, S. (Elsevier, 2007)
Background: The adoption of health-enhancing behaviours is essential to reduce the likelihood of recurrent coronary events. Aims: This study assessed the magnitude of health behaviour change 6 months following a first acute myocardial infarction (AMI), and examined differences between cardiac rehabilitation attendees and non-attendees. Methods: One hundred and six first AMI patients (males n=76, Australian-born n=71) participated in a 6-month follow-up of a descriptive longitudinal survey. Data on non-smoking behaviour, weight normalisation, adequate physical activity, low dietary fat intake, medication adherence and cardiac rehabilitation attendance were collected. The magnitude of change in health-enhancing behaviours from baseline to follow-up was calculated. Results: Whilst there was an overall increase in health-enhancing behaviours at the 6-month follow-up (P<0.001), nonsmoking behaviour, low dietary fat intake and medication adherence were more likely to be achieved than adequate physical activity and weight normalisation. Attendees at cardiac rehabilitation were more likely to report positive lifestyle change (P=0.001) and feeling healthier (P=0.040) than nonattendees. Conclusion: The wide variation in the adoption of health-enhancing behaviours at the 6-month follow-up suggested that participants were selective about which behaviours they changed. Cardiac rehabilitation personnel need to emphasise the importance of undertaking all healthenhancing behaviours in order to maximise their multiplicative benefits. © 2006 European Society of Cardiology. Published by Elsevier B.V. All rights reserved.